Spaces, places and possibilities: A participatory approach for developing and using integrated models for community planning. (April 2020) - Newell, Robert; Picketts, Ian
Abstract: Integrated models can support community planning efforts because they have the ability to elucidate social, economic, and environmental relationships and outcomes associated with different local development plans and strategies. However, deciding what to include in an integrated model presents a significant challenge, as including all aspects of a community and local environment is unfeasible, whereas including too few aspects leads to a non-representative model. This research aimed to address this challenge by employing an iterative, participatory process in an integrated modelling effort. Conducted in Squamish (BC, Canada), the research involved developing a community systems model and scenarios (i.e., different community development patterns), modelling the scenarios, evaluating the model through a community focus group, and refining the model and scenarios based on the feedback. Much of the work developing the initial systems model and scenarios was done a previous research phase, and it involved assembling local government and community stakeholder focus groups to discuss issues and possible futures for Squamish. Analysis of the focus group data informed the design of a community systems model and local development scenarios, which were subsequently applied in an integrated modelling exercise. Modelling primarily used ArcGIS and R, and explored a variety of factors including access to amenities, education, walkability, parks/trails, food and farm systems, public transit, housing affordability, threats to critical habitat, etc. Another local government and community stakeholder focus group was held to solicit feedback on the model and scenarios, which were then refined based on the feedback. The research found the participatory approach to beneficial for creating community planning tools with high relevance to local contexts and needs. The model developed in this work has great potential for supporting community planning because it effectively identifies the co-benefits and trade-offs of different development strategies. It is important to develop these types of community planning tools through iterative processes, where they are refined through multiple stages of feedback by a variety of stakeholders, to better capture the local concerns and realities of a place.